2010
DOI: 10.1002/jhm.612
|View full text |Cite
|
Sign up to set email alerts
|

Do hospitalists affect clinical outcomes and efficiency for patients with acute upper gastrointestinal hemorrhage (UGIH)?

Abstract: BACKGROUND Care by hospitalists has been associated with improved/similar clinical outcomes and efficiency. However, less is known about their effect on conditions dependent upon specialists for procedures/treatment plans. Our objective was to compare care for upper gastrointestinal hemorrhage (UGIH) patients attended by academic hospitalists and non-hospitalists. METHODS The study included 450 UGIH patients admitted to general medical services of 6 teaching hospitals. Outcomes included in-hospital mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Five of the eight articles which examined complications or adverse events found no significant differences between providers [51,67,82,86,89]. Huddleston et al [48] observed a reduction in surgical complications in orthopaedic patients whose postoperative medical care was managed by hospitalists.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the eight articles which examined complications or adverse events found no significant differences between providers [51,67,82,86,89]. Huddleston et al [48] observed a reduction in surgical complications in orthopaedic patients whose postoperative medical care was managed by hospitalists.…”
Section: Resultsmentioning
confidence: 99%
“…As the hospitalist model has rapidly disseminated nationally, the outcomes may also have changed. A recent prospective analysis of hospitalist care for patients with upper gastrointestinal hemorrhage at 6 academic hospitals also found higher readmission rates in the patients assigned to hospitalists (34). We also found a higher rate of readmissions after hospitalist care in patients with stroke (35).…”
Section: Discussionmentioning
confidence: 99%
“…Because these discharge decisions directly affect the LOS and readmission risk, we measured the service at discharge rather than the service responsible for an earlier component of care, such as the ICU service or admitting provider. 30 The key strength of this study is that we accurately measured trainee involvement and the service type responsible for each patient discharge. Studies using claims data have typically assigned hospital encounters to provider type by the individual provider's billing volume 16,17 or percent time-on-service.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using claims data have typically assigned hospital encounters to provider type by the individual provider's billing volume 16,17 or percent time-on-service. 30 This approach cannot account for factors such as leave periods, non-clinical duties, or part-time employment, and it cannot distinguish hospitalist-preceptor from hospitalist-alone care. We adjusted for multiple patient-level factors, including ICU transfer and historical information on comorbidities; accounted for clustering at both the patient and physician levels; and excluded protracted hospitalizations for social reasons.…”
Section: Discussionmentioning
confidence: 99%